PENGARUH STRES KERJA TERHADAP KEPUASAN KERJA DENGAN SUMBER DUKUNGAN SOSIAL SEBAGAI VARIABEL MODERATING - Novaritpraja, Gilang Yuda (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract One way to improve the performance of the HR is to pay attention to employee satisfaction. Job satisfaction is an important factor in HR to produce the optimal performance. If this employee fells dissatisfaction, it can cause work stress and make employees leave the company. Therefore, social support is needed to manage the level of stress from work in company environment.This research was held in PT. Charoen Pokphand Jaya Farm to find out wether there is an influence betwee job stress to job satisfaction wit a source of social support as a moderating variable. The sample of tis study was 40 hatchery employees, and using a censuss method. Researchers analyzed and calculated with regression.The result of tis study refer to the formulated hypothesis that job stress has a negative effect on job satisfaction, and social support can reduce job stress and social support has a positive influence to job satisfaction of employees. On the analysis result which used t-test showed that job stress and the interaction between job stress and social support has a influence to job satisfaction. Keyword : Job Stress, Social Support, Job Satisfaction.